Primary duodenal tuberculosis presenting as gastric-outlet obstruction: Its diagnosis - Vijai Datta Upadhyaya; Basant Kumar; Richa Lal; Moniak Sen Sharma; Mangal Singh; Rudramani (Wolters Kluwer Medknow Publications, 2013)
Introduction: Gastrointestinal tuberculosis often involves the ileocecal region. Duodenal and gastric tuberculosis found in only 1% of patients suffering from pulmonary tuberculosis with associated HIV infection in non-endemic areas. Duodenal obstruction due to tuberculosis is very rare and needs high index of suspicions for diagnosis. Mostly this entity is suspected on intraoperative findings. In this manuscript we emphasized on ways and means for establishing histopathological diagnosis before starting anti-tubercular treatment in such cases. Method and Material: All patients of suspected gastroduodenal tuberculosis presented with feature of gastric-outlet obstruction managed during Jan 2009 to June 2011 were included in the study. After proper evaluation (routine hematological and biochemical examination, microbiological examination, serological and endoscopic evaluation) exploratory laparotomy was done and if there is no mesenteric lymphadenopathy or it is not safe to take biopsy form the diseased duodenum, multiple FNAC were taken from the diseased portion for histopathological and microbiological diagnosis. Result: A total of five patients were treated during this period. The most common presentation was vomiting followed by failure to thrive and weight loss; two patients had abdominal pain. Biopsy of mesenteric lymph node was possible in two cases. FNAC from diseases portion was taken in all cases. FNAC showed granulomas in four cases. Cases where even FNAC finding was non-conclusive on HPE/Microbiology was not subjected to antitubercular drug. Conclusion: Multiple intra-operative FNAC may be taken from the diseased portion of the duodenum to establish the histopathological diagnosis if diagnosis is not established by any other mean.